THE DEVELOPMENT OF NURSING: FROM TRADITIONAL CAREGIVERS TO CONTEMPORARY EXPERTS - Waleed Sneed Khalifa Al-Shammari, Sahar Bunaydir Sanad Alharbi, Adel Ali Khalifa Al-Enezi, Abdulaziz Gathaith Al Mutairy, Muteb Darwish Sulaiman Alshammari, Hamad Mastor Dakelalah Daljuaid, Meshal Darwish Sulaiman Alshammari,; Afrah Sewilm Awad Alrasheedi, Mona Funaytil Mohammed Aljameeli, Fawaz Battah Alshammari, Ali Muteb Almutairi, Nasser Mohammed Aldhafiri, Maha Adai F Aldhafeeri, (Chelonian Research Foundation, 2022)
This research examines the historical evolution of nursing, following its path from early civilizations' use of caregivers to the formation of contemporary nursing as a scientific field. Examined is the impact of social movements, religious ideologies, and notable individuals such as Florence Nightingale on the development of nursing practice. The introduction of contemporary nursing methods to Ethiopia is also briefly discussed in the it. Keywords: Ethiopia, healthcare development, nursing history, Florence Nightingale, nursing procedure